Gastrointestinal nervous system α-synuclein as a potential biomarker of Parkinson disease. Issue 28 (July 2018) - Yan, Fudong; Chen, Ying; Li, Min; Wang, Yingqing; Zhang, Wenmin; Chen, Xiaochun; Ye, Qinyong
Abstract : Abstract: Lewy bodies (LB) play an essential role in the development, survival, and function maintenance of midbrain dopaminergic (DA) neurons in Parkinson disease (PD). Alpha-synuclein (α-synuclein) is the major component of Lewy bodies and is a potential target for Parkinson's disease (PD) therapies. α-synuclein can be detected in the gastrointestinal (GI) nervous system, but whether there is any association between altered α-synuclein expression in the GI nervous system and the onset of PD is not known. The answer to this question presents the opportunity for a promising biomarker in the pre-clinical diagnosis of PD. As such, this study aimed to measure the α-synuclein level in the GI nervous system of Parkinson's disease patients. The protein levels of α-synuclein in the GI nervous system of 31 PD patients (PD group) and 32 patients without PD or Parkinsonism-plus syndrome (control group) were evaluated via immunohistochemical staining. The χ 2 test was performed to evaluate the differences between the PD group and control group. In addition to the distribution of α-synuclein positive protein, regional distribution of the protein in the stomach was also evaluated across groups. Alpha synuclein overexpression was found in the GI nervous tissue of PD patients. The PD group included 17 positive results and 14 negative results. The control group exhibited 7 positive results and 24 negative results. The χ 2 test showed that χ 2  = 7.255, P  = .01. The distribution of these positive cases in the gastrointestinal system, the χ 2 test showed that P  = .949. The 21 stomach tissues had 7 α-synuclein positive protein tissues, while the body of stomach (4 α-synuclein positive protein) was higher than in other regions. Aberrant expression of α-synuclein was detected in the GI tissues of PD patients, though the distribution of α-synuclein in the gastrointestinal tract had no specificity. Gastrointestinal mucous biopsy could be regarded as a potential opportunity for the early-stage diagnostic exploration of PD, through the detection of α-synuclein inclusions.